Factors associated with memory of informal caregivers: A scoping review protocol. - Dingyue Wang; Sharron Rushton; Leila Ledbetter; Margaret Graton; Kimberly Ramos; Cristina C Hendrix (PLoS ONE)
The ability to retain and remember information (memory) is essential to caregiving tasks. There is evidence that caregivers are at greater risk for experiencing deteriorations in cognitive status than non-caregivers, especially memory; however, we have a limited understanding of factors that are related to changes in caregiver memory. This scoping review intends to comprehensively map factors related to caregiver memory reported in the literature within the chronic caregiving context. Specific aims include (1) identifying factors related to caregiver memory; (2) examining how caregiver memory has been measured; and (3) describing changes in caregiver memory during their caregiving period. This review will be conducted following Arksey and O'Malley's framework and reported using the PRISMA guidelines for Scoping Reviews (PRISMA-ScR). Studies will be included if (1) the studies focus on home-based unpaid long term family caregiving; (2) study participants (patients), of any age, have one (or more) chronic illness or disability and receive care from a caregiver for 6 months or more; (3) caregivers are adults (> = 18 years of age). Any chronic disease or condition will be included. The search will encompass gray literature and peer-reviewed literature in MEDLINE (via Ovid), CINAHL Plus with Full Text (via EBSCOhost), Embase (via Elsevier), APA PsycINFO (via EBSCOhost), Sociology Source Ultimate (via EBSCOhost), and ProQuest Dissertations and Theses Global. Data extraction will include specific details about the participants, concept, context, study methods, and key caregiver-related findings. The Caregiver Health Model will provide a framework to categorize factors that impact caregivers' memory including caregiver health promotion activities, caregiver attitudes and beliefs, caregiver task, and caregiver needs. Factors that do not fall into the Caregiver Health Model domains will be organized by emerging themes.